2018
DOI: 10.3390/life8010003
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of a Compartmentalized Host-Parasite Replicator System under Periodic Washout-Mixing Cycles

Abstract: The emergence and dominance of parasitic replicators are among the major hurdles for the proliferation of primitive replicators. Compartmentalization of replicators is proposed to relieve the parasite dominance; however, it remains unclear under what conditions simple compartmentalization uncoupled with internal reaction secures the long-term survival of a population of primitive replicators against incessant parasite emergence. Here, we investigate the sustainability of a compartmentalized host-parasite repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…The emergence of parasitic replicators are believed to be inevitable and crucial in an evolving replicator system [6] as experimentally demonstrated in an artificial RNA replication system we have reported [22]. Theoretical studies have predicted that spatial structures, such as cell-like compartments, can allow survival of host replicators in the presence of parasites [23][24][25][26]. Recent experimental studies using the RNA replication system confirmed this; compartmentalization actually supported the survival of functional RNA replicators in the presence of spontaneously emerging parasitic RNA replicators [27][28][29].…”
Section: Introductionmentioning
confidence: 65%
“…The emergence of parasitic replicators are believed to be inevitable and crucial in an evolving replicator system [6] as experimentally demonstrated in an artificial RNA replication system we have reported [22]. Theoretical studies have predicted that spatial structures, such as cell-like compartments, can allow survival of host replicators in the presence of parasites [23][24][25][26]. Recent experimental studies using the RNA replication system confirmed this; compartmentalization actually supported the survival of functional RNA replicators in the presence of spontaneously emerging parasitic RNA replicators [27][28][29].…”
Section: Introductionmentioning
confidence: 65%
“…However, when a hypercycle is compartmentalized appropriately, the parasitic replicators are isolated from other normal hypercycles, and hypercyclic replication can be sustained . This effect of compartmentalization to suppress parasitic replicators has also been investigated theoretically for other self‐replication systems by Szathmary's and Hogeweg's groups …”
Section: Compartmentalizationmentioning
confidence: 99%
“…[94][95][96] This effect of compartmentalization to suppress parasitic replicators has also been investigated theoretically for other self-replication systems by Szathmary's and Hogeweg's groups. [97][98][99][100][101][102][103] Experimental verification of compartmentalization has been reported. Since 1995, several groups have reported biochemical reactions in microscale compartments, such as lipid-bilayer vesicles (liposomes) or water-in-oil droplets.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…As This class of multilevel selection describes several mechanisms proposed in scenarios for the origins of life, based on various types of compartments (e.g. lipid vesicles [20], pores [21,22], inorganic compartments [23], coacervates [2,4] or aerosols [24]) or various protocols of transient compartmentalization [25,26]. Particularly exciting is the recent experiment that demonstrated the mechanism for the first time, in which small droplets containing RNA in a microfluidic device [17] were used as compartments.…”
Section: Introductionmentioning
confidence: 99%